2019
DOI: 10.1155/2019/7250563
|View full text |Cite
|
Sign up to set email alerts
|

Wide Variation of Squeezing Force and Dispensing Time Interval among Eyedropper Bottles

Abstract: Purpose. We aimed to investigate squeezing force and dispensing time interval of the first and second eye drops among a variety of eyedropper bottles and to clarify associated factors within these parameters. Methods. A total of 87 eyedropper bottles were involved in this study. We developed a squeezing force measuring system consisting of a syringe pump, digital force gauge, and custom-made test stand to measure the squeezing force and dispensing interval. The eyedropper bottle was housed in the system vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition to aging [ 21 ], some musculoskeletal or neurological diseases may increase instillation failure. It has been reported that the force required to expel eyedrops sometimes exceeds the ability of some healthy subjects [ 22 ] and that the squeezing force of eyedropper bottles is very wide [ 23 , 24 ]. Approximately 20% of ophthalmic patients reported difficulty squeezing their eyedrop bottle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to aging [ 21 ], some musculoskeletal or neurological diseases may increase instillation failure. It has been reported that the force required to expel eyedrops sometimes exceeds the ability of some healthy subjects [ 22 ] and that the squeezing force of eyedropper bottles is very wide [ 23 , 24 ]. Approximately 20% of ophthalmic patients reported difficulty squeezing their eyedrop bottle.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of a single dose is 30 μL. However, the porous gasket and hydrophilic membrane create significant resistance in the path of the drug flow, resulting in a fixed actuation force in the range of 17-20 N, which is lower than that of the Comod® and 3K® systems (41). One disadvantage of this technology is that the gasket and membrane structures may limit the use of low-viscosity formulations.…”
Section: Multidose Ampoulesmentioning
confidence: 99%